2010
DOI: 10.1186/1475-2875-9-287
|View full text |Cite
|
Sign up to set email alerts
|

Fine specificity of anti-MSP119 antibodies and multiplicity of Plasmodium falciparum Merozoite Surface Protein 1 types in individuals in Nigeria with sub-microscopic infection

Abstract: BackgroundThe absence of antibodies specific for the 19 kDa C-terminal domain of merozoite surface protein 1 (MSP119) has been associated with high-density malaria parasitaemia in African populations. The hypothesis that a high prevalence and/or level of anti-MSP119 antibodies that may inhibit erythrocyte invasion would be present in apparently healthy individuals who harbour a sub-microscopic malaria infection was tested in this study.MethodsPlasma samples were collected from residents in a region in Nigeria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
2
6
1
Order By: Relevance
“…The identification of more than one genotype of MSP-1 (block 2) and MSP-2 (block 3) genes among the samples portrayed the genetic diversity of parasite genotypes that exist among patients infected with P. falciparum. This is consistent with other studies where allelic variants of MSP-1 and MSP-2 have been reported in other countries [13,28,39,[40][41][42] though not specifically among HIV-patients. The genetic diversity of P. falciparum populations and the complexity of infection have been reported to vary according to the intensity of transmission in different geographical areas with the existence of size polymorphism as identified by the size of the PCR amplified fragment [10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 82%
“…The identification of more than one genotype of MSP-1 (block 2) and MSP-2 (block 3) genes among the samples portrayed the genetic diversity of parasite genotypes that exist among patients infected with P. falciparum. This is consistent with other studies where allelic variants of MSP-1 and MSP-2 have been reported in other countries [13,28,39,[40][41][42] though not specifically among HIV-patients. The genetic diversity of P. falciparum populations and the complexity of infection have been reported to vary according to the intensity of transmission in different geographical areas with the existence of size polymorphism as identified by the size of the PCR amplified fragment [10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 82%
“…Our discovery of multiple independent loci of avian Plasmodium parasites provides insight into species limits, levels of differentiation, and gene‐flow among parasite populations. Allelic variation at a gene locus such as MSP1, which is known to be linked to immunity (Ngoundou‐Landji et al ) as well as being a protein involved in the invasion of the red blood cells (Kadekoppala and Holder , Wright and Rayner ), allows us to study how this variation might be linked to differences in host–parasite interactions. Such studies are crucial to understanding the evolution of local patterns of virulence and host resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The MSP1 gene encodes a 190 kDa protein that during erythrocytic schizogony (merogony) is anchored to the parasite's cell membrane (Gerold et al ). Antibodies to the peptide are frequent in human populations with high malaria prevalence and can be associated with resistance to the parasite (Hui and Hashimoto , Ngoundou‐Landji et al ). Because MSP1 is one of the major proteins that coats the parasite during its extracellular state and is associated with the initial attachment to host red blood cells, it is likely to interact with the immune system and parasite evasion mechanism of the host.…”
mentioning
confidence: 99%
“…Including both variants of MSP1 19 in the vaccine does not lead to an improved immunogenicity profile with respect to coverage. However, if the DiCo principle applies, use of a combination of two or more engineered MSP1 19 modules may still be beneficial, as the combination could target the immune response to epitopes of choice, enabling the fine specificity that is deemed necessary to make an MSP1 19 -based vaccine work (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%